Novel potent (dihydro)benzofuranyl piperazines as human histamine receptor ligands – Functional characterization and modeling studies on H3 and H4 receptors. (15th January 2021) - Corrêa, Michelle F.; Balico-Silva, André L.; Kiss, Dóra J.; Fernandes, Gustavo A.B.; Maraschin, Jhonatan C.; Parreiras-e-Silva, Lucas T.; Varela, Marina T.; Simões, Sarah C.; Bouvier, Michel; Keserű, György M.; Costa-Neto, Claudio M.; Fernandes, João Paulo S.
Graphical abstract: Highlights: Allylpiperazine analogues of LINS01 compounds are potent H3 receptor antagonists. The benzofuranyl-piperazinecarboxamide 2c is a partial agonist at H4 receptor. Docking studies with LINS01 compounds were performed. Structure activity relationships for LINS01 series are discussed. Ligand efficiency analysis was performed. Abstract: Histamine acts through four different receptors (H1 R-H4 R), the H3 R and H4 R being the most explored in the last years as drug targets. The H3 R is a potential target to treat narcolepsy, Parkinson's disease, epilepsy, schizophrenia and several other CNS-related conditions, while H4 R blockade leads to anti-inflammatory and immunomodulatory effects. Our group has been exploring the dihydrobenzofuranyl-piperazines (LINS01 series) as human H3 R/H4 R ligands as potential drug candidates. In the present study, a set of 12 compounds were synthesized from adequate (dihydro)benzofuran synthons through simple reactions with corresponding piperazines, giving moderate to high yields. Four compounds (1b, 1f, 1g and 1h ) showed high hH3 R affinity (p K i > 7), compound 1h being the most potent (p K i 8.4), and compound 1f showed the best efficiency (p K i 8.2, LE 0.53, LLE 5.85). BRET-based assays monitoring Gαi activity indicated that the compounds are potent antagonists. Only one compound (2c, p K i 7.1) presented high affinity for hH4 R. In contrast to what was observed for hH3 R, it showed partial agonist activity. Docking experiments indicated that bulky substituents occupy a hydrophobic pocket in hH3 R, while the N -allyl group forms favorable interactions with hydrophobic residues in the TM2, 3 and 7, increasing the selectivity towards hH3 R. Additionally, the importance of the indole NH in the interaction with Glu5.46 from hH4 R was confirmed by the modeling results, explaining the affinity and agonistic activity of compound 2c . The data reported in this work represent important findings for the rational design of future compounds for hH3 R and hH4 R.